Efficacy of Nigella sativa Enrichment of Live Tubifex sp. to Enhance Larval Performance of Hemibagrus nemurus - Safitriani Safitriani; Rini Hertati; Mohammad Yusuf Amrullah; Khairul Hadi (Program Studi Budidaya Perairan Universitas Mataram, 2025)
The growth and survival of catfish larvae (Hemibagrus nemurus) are important factors in successful cultivation, which are greatly influenced by the quality of the natural feed provided. This study evaluated the effect of providing live feed Tubifex sp. enriched with Nigella sativa solution on the growth and survival of catfish larvae. Seven-day-old fish larvae were fed with various doses of Nigella sativa enrichment (0; 0.1; 0.2; 0.3; and 0.4 mg) for 21 days using a completely randomized design with three replications. The parameters observed included absolute weight, absolute length, specific growth rate, and survival. The results showed that Tubifex sp. feed enriched with Nigella sativa solution significantly increased all parameters of larval growth and survival, with the optimal dose at 0.2 mg. This increase is thought to be related to the content of the bioactive compound thymoquinone in Nigella sativa which functions as an antioxidant and immunostimulant, leading to increased metabolic capacity and resistance of larvae to environmental stress. This finding provides an innovative alternative to natural feed that is more nutritious and effective in cultivating catfish, while also supporting sustainable and environmentallyfriendly aquaculture practices.